Switching to efficient technologies in traditional biomass intensive countries: The resultant change in emissions. (1st May 2017) - Cutz, L.; Masera, O.; Santana, D.; Faaij, A.P.C.
Abstract: This paper aims to quantify the benefits of switching from a system dependent on traditional biomass to systems running on more efficient fuels and technologies. It is estimated that even when open fires burning fuelwood are replaced by improved cooking stoves (ICSs) and liquefied petroleum gas (LPG) stoves, and biomass is processed in dedicated biomass power plants, a net reduction in CO2 emissions is still obtained. The ICS/LPG stove/biomass combustion power plant configuration could provide an average net reduction of 84 kg-C e /tDM. Meanwhile, a net reduction of 105 kg-C e /tDM could be obtained when implementing a ICS/LPG stove/biomass gasification power plant scheme. Main factors influencing the net reduction of CO2 emissions are technology efficiency and the fraction of non-renewable fuelwood use. The switch from traditional biomass to modern biomass in traditional biomass intensive countries must not only be done to reduce CO2 emissions but also to avoid indoor pollution and energy poverty. Health improvements should be more important than energy savings. Results also indicate that the use of modern biomass systems not only could provide a reduction of local environmental pollution, but also could boost the local economy by the creation of biomass infrastructures. Highlights: Health improvements should be more important than energy savings. Systems with stacking patterns can still provide a net reduction in CO2 emissions. Main factors affecting the CO2 abatement potential are technology efficiency and fNRB. Modern biomass systems will require institutional strengthening.